KESİRLİ DİFERİNTEGRAL YARDIMIYLA CHEBYSHEV DENKLEMİNİN AÇIK ÇÖZÜMLERİ - ÇAPAN, EMİNE (Fırat Üniveristesi, 2018)
Matematiksel analizin bir kolu olan kesirli analiz, türev ve integralin tam sayı olmayan (keyfi) mertebelere genişletilmiş halidir. Fen ve mühendislikte oldukça geniş uygulama alanına sahiptir. Amacımız kesirli analiz yardımı ile singüler katsayılı bazı denklemler için farklı çözümler elde etmek ve literatüre kazandırmaktır. Bu tezde, verilen bazı homojen kesirli diferintegral denklemlerin özel çözümlerinin elde edilişinden ve bu çözümlerin denklemi sağladığından bahsedilmiştir. Daha sonra singüler katsayılı homojen ve homojen olmayan Chebyshev denkleminin farklı açık çözümleri kesirli analizin tanım, teorem, özellikleri ve Leibniz kuralı yardımı ile elde edilmiştir. Ayrıca, homojen Chebyshev denkleminin açık çözümlerinin başka bir gösterimi olan hipergeometrik gösterim gama fonksiyonunun özellikleri ve Leibniz kuralı yardımı ile bulunmuştur.

Fractional analysis which is a branch of mathematical analysis is an extension of the derivative and integral to non-integer (arbitrary) order. It has a wide application area in science and engineering. Our aim is to obtain different solutions for some singular coefficient equations with the aid of fractional analysis and to gain it to literature. In this thesis, it is mentioned that certain solutions of given homogeneous fractional differintegral equations are obtained and these solutions provide the equations. Then, different explicit solutions of the homogeneous and nonhomogeneous Chebyshev equation with singular coefficients were obtained with the aid of definition, theorems and properties of fractional analysis and Leibniz's rule. In addition, the hypergeometric representation, which is another representation of the explicit solutions of the homogeneous Chebyshev equation was found with the help of properties for gamma function and Leibniz's rule.
Explicit solutions of Chebyshev equations by fractional differintegral
Keywords: Matematik